Bodies - Saglia, Diego (Romanticism on the Net)

(untitled) (Université de Montréal, 2023)
Drawing on selected objects from RÊVE (Romantic Europe: The Virtual Exhibition), this essay discusses possible ways of exploring Romantic-period bodies through their material relics, including textual inscriptions, and immaterial traces such as sensations or memories. Its focus is on artefacts that enable us to outline narratives about culture-specific notions of the physical, as well as the experiences and affects associated with it. To this end, the essay focuses particularly on exhibits related to the mourning and memorializing of a (dead) beloved body – male or female, real or imagined, and treated seriously or comically – and how they testify to an intersection of competing, though interlaced, forms of dispersal and collection, fragmentation and recomposition. Among the objects examined are Teresa Guiccioli’s travelling chest, a medallion with Byron’s hair, Tippoo’s Tiger, and Thomas Hood’s poem “Mary’s Ghost.” This contribution explores a portion of the vast and heterogeneous cultural corpus of conceptions and experiences of the Romantic-era body in order to trace narratives of mediation and incompleteness that may open up unsuspected new approaches to, and interpretations of, Romantic-period corporealities.